Cultured states youth, gender, and modern style in 1960s Dar es Salaam - Ivaska, Andrew M. (Durham, NC Duke University Press, 2011)
Politics and culture--Tanzania--Dar es Salaam.
Includes bibliographical references (p. [253]-269) and index.
Keywords: Politics and culture--Tanzania--Dar es Salaam